Chemotherapy Influences the Pseudocapsule Composition in Soft Tissue Sarcomas - O’Donnell, Patrick W. (Springer US, 2013)
BACKGROUND: Soft tissue sarcomas are a heterogeneous group of malignant tumors. Standard treatment for soft tissue sarcoma of the extremity is surgical excision and adjuvant therapy; however, the role of neoadjuvant chemotherapy is controversial. QUESTIONS/PURPOSES: We sought to (1) define the histologic characteristics of the pseudocapsule in soft tissue sarcomas; (2) compare the appearance of this structure in chemotherapy-treated versus untreated soft tissue sarcomas; and (3) evaluate the effect of chemotherapy on the presence and viability of tumor cells at the host-sarcoma interface. METHODS: Twenty-eight patients with biopsy-proven, deep, high-grade extremity soft tissue sarcomas greater than 5 cm (AJCC stage III) treated with chemotherapy and surgical excision were compared histologically with 47 matched control subjects treated with surgery alone. RESULTS: A pseudocapsule was identifiable in the majority of tumors and consisted of two identifiable layers, each with specific histological characteristics suggesting the biologic processes occurring in these layers are different. The pseudocapsule was more frequently observed in the group treated with chemotherapy and it was more frequently continuous, thicker, and better developed in this group. Chemotherapy decreased the number of tumors with malignant cells identified within and beyond the pseudocapsule. CONCLUSIONS: Neoadjuvant chemotherapy contributed to the development of a pseudocapsule and decreased the number of tumors with malignant cells identified within and beyond the pseudocapsule. CLINICAL RELEVANCE: These findings may provide a histological explanation for the clinical effect of chemotherapy in soft tissue sarcoma. LEVEL OF EVIDENCE: Level III, therapeutic study. See Guidelines for Authors for a complete description of levels of evidence.